Composite positive electrode active material, positive electrode containing the same, and all-solid-state battery containing the same
Patent Information
- Application Number
- KR1020240098955
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2024-05-10
- Filing Date
- 2024-07-25
- Publication Date
- 2026-09-18
- Estimated Expiration
- 2044-07-25
Smart Images

Figure 112024081405402-PAT00001_ABST
Abstract
Description
Technology Field
[0001] The present invention relates to a composite cathode active material, a cathode comprising the same, and an all-solid-state battery comprising the same. Background Technology
[0002] Recently, lithium-ion batteries have expanded their applications from power sources for small mobile devices to medium-to-large electric vehicles (EVs), hybrid electric vehicles (HEVs), and energy storage systems (ESS). In particular, interest in eco-friendly electric vehicles is rising significantly, and major global automakers are accelerating technological development by recognizing electric vehicles as a next-generation growth technology under the motto of environmental sustainability. Unlike small batteries, medium-to-large lithium-ion batteries operate under harsh conditions such as temperature and shock, and because they contain a large number of cells, ensuring safety is essential. Consequently, as the application scope of industries requiring lithium-ion batteries expands to include large-scale batteries, interest in the safety issues of lithium-ion batteries is also increasing significantly.
[0003] Conventional lithium-ion batteries utilize organic liquid electrolytes, which present problems such as low thermal stability, flammability, and leakage. In fact, explosion accidents involving products using these batteries are continuously being reported, making it urgent to resolve these issues. Accordingly, all-solid-state batteries, which use solid electrolytes, are emerging as a solution.
[0004] Sulfide-based solid electrolytes are receiving much attention as suitable materials for all-solid-state batteries due to their high ionic conductivity and soft mechanical properties, but they have electrochemically unstable characteristics. As a result, they can cause serious side reactions when in direct contact with 5V-class cathode active materials.
[0005] Accordingly, research is being developed to form an oxide-based solid electrolyte in a shell form on the cathode active material in order to prevent direct contact between the sulfide-based solid electrolyte and the 5V-class cathode active material.
[0006] However, while oxide-based solid electrolyte shells can suppress side reactions of sulfide-based solid electrolytes, there was a problem in that their low ionic conductivity caused them to act as a resistive layer inside the all-solid-state battery, leading to a degradation of the battery's performance. The problem to be solved
[0007] One embodiment provides a composite cathode active material having excellent ionic conductivity and electrochemical stability.
[0008] Another embodiment provides a positive electrode comprising the above-mentioned composite positive electrode active material.
[0009] Another embodiment provides an all-solid-state battery including the anode, having excellent charge / discharge characteristics and lifespan characteristics. means of solving the problem
[0010] A composite positive electrode active material according to one embodiment comprises a positive electrode active material; and a coating layer located on the surface of the positive electrode active material and comprising a compound represented by the following chemical formula 1.
[0011] [Chemical Formula 1]
[0012] LiX 1 -Li a M 1 X 2 b-c O c
[0013] In the above chemical formula 1,
[0014] X 1 and X 2 Each is independently F, Cl, Br, I, or a combination thereof, and
[0015] M 1 is B, Al, Ga, In, Ti, Zr, Hf, Fe, or a combination thereof, and
[0016] 0.01≤a≤10, 0.01≤b≤10, and 0≤c <b이다.
[0017] A positive electrode according to another embodiment comprises a positive electrode current collector; and a positive electrode active material layer located on the positive electrode current collector, wherein the positive electrode active material layer comprises the composite positive electrode active material.
[0018] A solid-state battery according to another embodiment comprises the positive electrode; the negative electrode; and a solid electrolyte layer located between the positive electrode and the negative electrode. Effects of the invention
[0019] The composite cathode active material according to one embodiment has the advantage of excellent ionic conductivity and electrochemical stability.
[0020] An all-solid-state battery according to another embodiment has the advantage of excellent charge / discharge characteristics and lifespan characteristics by including the composite cathode active material. Brief explanation of the drawing
[0021] FIG. 1 is a cross-sectional view of an all-solid-state battery according to one embodiment. Figure 2 is a graph showing the XRD evaluation results of the coating materials used in Synthesis Example 1 and Comparative Synthesis Example 1. Figure 3 is a graph showing the XRD evaluation results of the coating materials used in Synthesis Example 4 and Comparative Synthesis Example 4. Figure 4 is a graph showing the results of the ion conductivity evaluation of the coating materials used in Synthesis Example 1 and Comparative Synthesis Example 1. Figure 5 is a graph showing the results of the ion conductivity evaluation of the coating materials used in Synthesis Example 4 and Comparative Synthesis Example 4. Figure 6 is a graph showing the cyclic voltammetry evaluation results of the coating materials used in Synthesis Example 1, Comparative Synthesis Example 1, and Comparative Synthesis Example 2. Figure 7 is an image of the composite cathode active material prepared in Synthesis Example 1 observed using a Scanning Electron Microscope (SEM). FIG. 8 is (a) an image of the composite cathode active material prepared in Synthesis Example 1 analyzed by SEM-EDS (Energy Dispersive Spectrometer), (b) an image of Al mapping, (c) an image of Ni mapping, and (d) an image of Al and Ni mapping. Figure 9 shows the results of X-ray Photoelectron Spectroscopy (XPS) analysis for the composite cathode active material prepared in Synthesis Example 2. FIGS. 10 to 12 are graphs evaluating the initial charge-discharge characteristics of all-solid-state batteries prepared in Example 1, Example 2, and Example 3. Figure 13 is a graph evaluating the initial charge-discharge characteristics of the all-solid-state battery manufactured in Example 2 when it is charged to 5.0V and then discharged to 2.3V. Figure 14 is a graph evaluating the initial charge-discharge characteristics of the all-solid-state batteries prepared in Example 2 and Comparative Example 1. Figure 15 is a graph evaluating the initial charge-discharge characteristics of the all-solid-state battery manufactured in Comparative Example 2. Figure 16 is a graph evaluating the initial charge-discharge characteristics of the all-solid-state battery manufactured in Comparative Example 3. Figure 17 is a graph evaluating the initial charge-discharge characteristics of the all-solid-state battery manufactured in Example 4. Figure 18 is a graph evaluating the initial charge-discharge characteristics of the all-solid-state battery manufactured in Example 5. FIG. 19 is a graph evaluating the rate capability characteristics according to the charge-discharge cycle of the all-solid-state batteries prepared in Examples 1, 2, and 3. FIG. 20 is a graph evaluating the rate capability characteristics according to the charge-discharge cycle of the all-solid-state batteries prepared in Example 2 and Comparative Example 1. Figure 21 is a graph evaluating the rate capability characteristics according to the charge-discharge cycle of the all-solid-state batteries prepared in Example 2 and Comparative Example 2. FIG. 22 is a graph evaluating the rate capability characteristics according to the charge-discharge cycle of the all-solid-state batteries prepared in Example 1 and Comparative Example 3. Figure 23 is a graph evaluating the rate capability characteristics according to the charge-discharge cycle of the all-solid-state battery manufactured in Example 4. Figure 24 is a graph evaluating the rate capability characteristics according to the charge-discharge cycle of the all-solid-state battery manufactured in Example 5. Specific details for implementing the invention
[0022] The following embodiments are described in detail so that those skilled in the art can easily implement them. However, the structure actually applied may be implemented in various different forms and is not limited to the embodiments described herein.
[0023] In the drawing, the thickness is enlarged to clearly represent various layers and regions. When a part such as a layer, film, region, or plate is described as being "on" another part, this includes not only the case where it is "immediately on" another part, but also the case where there is another part in between. Conversely, when a part is described as being "immediately on" another part, it means that there is no other part in between.
[0024] To clearly explain the embodiments shown in the drawings, parts unrelated to the description have been omitted, and the same reference numerals have been used for identical or similar components throughout the specification.
[0025] In the following, the terms "lower" and "upper" are used for convenience of explanation only and do not limit positional relationships.
[0026] In the following, unless otherwise defined, 'metal' includes metals and semimetals.
[0027] In the following, "combination of these" may mean a mixture of components, a laminate, a composite, a copolymer, an alloy, a blend, and a reaction product, etc.
[0028] A composite cathode active material according to one embodiment is described below.
[0029] Composite cathode active material
[0030] A composite positive electrode active material according to one embodiment comprises a positive electrode active material; and a coating layer located on the surface of the positive electrode active material and comprising a compound represented by the following chemical formula 1.
[0031] [Chemical Formula 1]
[0032] LiX 1 -Li a M 1 X 2 b-c O c
[0033] In the above chemical formula 1,
[0034] X 1 and X 2 Each is independently F, Cl, Br, I, or a combination thereof, and
[0035] M 1 is B, Al, Ga, In, Ti, Zr, Hf, Fe, or a combination thereof, and
[0036] 0.01≤a≤10, 0.01≤b≤10, and 0≤c <b이다.
[0037] Previously, it was common practice to coat the surface of 5V-class cathode active materials with lithium chloride compounds, but lithium chloride compounds had the problem of insufficient electrochemical stability. In addition, when lithium fluoride compounds were coated instead of the lithium chloride compounds, while electrochemical stability could be improved, there was a problem that the low lithium ion conductivity could increase resistance inside the battery.
[0038] Accordingly, in one embodiment, a composite active material is provided by coating a composite fluoride-based compound on the surface of a 5V-class positive electrode active material to increase electrochemical stability while achieving high ion conductivity.
[0039] The compound represented by the above chemical formula 1 is It may be a compound in which a lithium halide and a lithium metal halide (e.g., lithium metal fluoride or lithium metal oxyfluoride) are combined. For example, the compound represented by Chemical Formula 1 above is a compound in which a lithium halide and a lithium metal fluoride are combined. Since it has a higher lithium ion conductivity than lithium fluoride, when used as a coating material for a positive electrode active material, it may not degrade the performance of the all-solid-state battery.
[0040] When such a composite cathode active material is applied to an all-solid-state battery, the composite cathode active material has high electrochemical stability, so side reactions with the solid electrolyte are suppressed, thereby enabling the realization of an all-solid-state battery with excellent performance.
[0041] X in the above chemical formula 1 1 and X 2 They may differ from each other.
[0042] In one embodiment, the compound represented by Chemical Formula 1 may include a compound represented by Chemical Formula 1A below.
[0043] [Chemical Formula 1A]
[0044] LiCl-Li a M 1 F b-c O c
[0045] In the above chemical formula 1A,
[0046] M 1 is B, Al, Ga, In, Ti, Zr, Hf, Fe, or a combination thereof, and
[0047] 0.01≤a≤10, 0.01≤b≤10, and 0≤c <b이다.
[0048] For example, the compound represented by the above chemical formula 1A may include the compound represented by the following chemical formula 1A-1, the compound represented by the chemical formula 1A-2, or a combination thereof.
[0049] [Chemical Formula 1A-1]
[0050] LiCl-Li a AlF b
[0051] [Chemical Formula 1A-2]
[0052] LiCl-Li a TiF b
[0053] In the above formula 1A-1 or the above formula 1A-2,
[0054] 0.01≤a≤10 and 0.01≤b≤10.
[0055] For example, the compound represented by the above chemical formula 1 may include the compound represented by the following chemical formula 1B-1, the compound represented by the chemical formula 1B-2, or a combination thereof.
[0056] [Chemical Formula 1B-1]
[0057] LiF 1-x1 Cl x1 -Li a TiF b
[0058] In the above chemical formula 1B-1, 0.01≤a≤10, 0.01≤b≤10, and 0 <x1<1이고,
[0059] [Chemical Formula 1B-2]
[0060] LiCl-Li a TiF b1-x2 Cl x2
[0061] In the above chemical formula 1B-2, 0.01≤a≤10, 0.01≤b1≤10, and 0 <x2<b1이다.
[0062] For example, the compound represented by the above chemical formula 1 may include a compound represented by the following chemical formula 1C.
[0063] [Chemical Formula 1C]
[0064] LiCl-Li a TiF b2-x3-c1 Cl x3 O c1
[0065] In the above chemical formula 1C,
[0066] 0.01≤a≤10, 0.01≤b2≤10, and 0≤x3 <b2, 0<c1<b2 이다.
[0067] As a specific example, the compound represented by the above chemical formula 1 is LiCl-Li3AlF6, LiCl-Li2TiF6 , LiCl-Li2ZrF6, LiCl-Li3FeF6, LiCl-Li2Zr 0.5 Ti 0.5 F6, LiCl-Li3Al 0.5 Fe 0.5 F6, LiCl-Li3HfF6, LiCl-Li2TiF 5.6 O 0.2, Or it may include a combination of these.
[0068] For example, in the compound represented by the above chemical formula 1, LiX 1 and Li a M 1 X 2 b-c O c It may be included in a molar ratio of 1:1 to 1:9, for example, in a molar ratio of 1:2 to 1:5, a molar ratio of 1:3 to 1:5, or a molar ratio of 1:3 to 1:4.
[0069] In one embodiment, the lithium ion conductivity of the compound represented by Formula 1 is 1.0 x 10⁻⁶ -6 It may be greater than S / cm, for example, 2.0X10 -6 S / cm or higher, 5.0X10 -6 S / cm or higher, 1.0X10 -5 It can be greater than S / cm, and there is no upper limit.
[0070] For example, the above-mentioned positive electrode active material may include a lithium-rich positive electrode active material or a high-nickel (High-Ni) positive electrode active material.
[0071] For example, the positive electrode active material may include a lithium nickel-based oxide, a lithium cobalt-based oxide, a lithium manganese-based oxide, a lithium iron phosphate-based compound, a cobalt-free lithium nickel-manganese-based oxide, or a combination thereof, and for example, may include lithium nickel oxide (LNO), lithium cobalt oxide (LCO), lithium nickel cobalt oxide (NC), lithium nickel cobalt aluminum oxide (NCA), lithium nickel cobalt manganese oxide (NCM), lithium nickel manganese oxide (NM), lithium manganese oxide (LMO), lithium iron phosphate oxide (LFP), or a combination thereof.
[0072] In one embodiment, the positive active material may include a spinel-based positive active material, and the spinel-based positive active material may include a compound represented by the following chemical formula 2A.
[0073] [Chemical Formula 2A]
[0074] Li d M 2 e Mn 2-e O 4-f A f
[0075] In the above chemical formula 2A,
[0076] M 2 is Al, Ni, Co, Mn, Zn, Cr, Mg, Sr, V, Ca, Ti, Y, Zr, Nb, Mo, Hf, Ta, W, Na, Sn, rare earth elements, or combinations thereof, and
[0077] A is F, Cl, Br, or I, and
[0078] 1≤d≤2, 0≤e<2, and 0≤f<4.
[0079] For example, the above positive active material may include a layered positive active material, and the layered positive active material may include a compound represented by the following chemical formula 2B.
[0080] [Chemical Formula 2B]
[0081] Li d1 Nie1 M 3 e2 Mn e3 O 2-f1 A f1
[0082] In the above chemical formula 2B,
[0083] M 3 is Al, Co, Mn, Zn, Cr, Fe, Mg, Sr, V, Ca, Ti, Y, Zr, Nb, Mo, Hf, Ta, W, Na, Sn, rare earth elements, or combinations thereof, and
[0084] A is F, Cl, Br, I, F, S, P, or a combination thereof, and
[0085] 1≤d1≤2, 0〈e1≤1, 0〈e2≤1, 0〈e3≤1, and 0≤f1〈2.
[0086] As a specific example, the above-mentioned positive active material is LiNi 0.5 Mn 1.5 It may include O4, LiCoMnO4, or a combination thereof.
[0087] For example, the positive active material may be in the form of particles, and the positive active material may include a single crystal, a polycrystalline material composed of an assembly thereof, or a combination thereof.
[0088] The above single crystal may refer to the smallest unit of particles constituting the positive active material, and may refer to the smallest unit determined from the external geometric shape.
[0089] The average particle size (D50) of the positive active material in the form of a single crystal may be 4㎛ to 10㎛, for example 5㎛ to 10㎛, or 5㎛ to 8㎛.
[0090] The average particle size (D50) of the positive active material in a polycrystalline form may be 10㎛ to 20㎛, for example 12㎛ to 20㎛, or 12㎛ to 18㎛.
[0091] Here, the average particle size may be obtained by selecting approximately 20 random particles from a scanning electron microscope image of the positive electrode active material, measuring their particle sizes (diameter, or major axis, or length of the major axis), obtaining a particle size distribution, and taking the diameter (D50) of the particle with a cumulative volume of 50% from the particle size distribution as the average particle size.
[0092] In one embodiment, the coating layer may be included in an amount of 1 to 20 parts by weight with respect to 100 parts by weight of the positive active material, for example, 5 to 20 parts by weight, 1 to 15 parts by weight, or 5 to 15 parts by weight.
[0093] If the above numerical range is satisfied, a composite cathode active material with excellent electrochemical stability and ionic conductivity can be realized.
[0094] Method for manufacturing a composite cathode active material
[0095] The following describes a method for manufacturing a composite cathode active material.
[0096] A method for manufacturing a composite positive electrode active material according to one embodiment comprises: (1) a step of manufacturing a compound represented by the chemical formula 1 described above; and (2) a step of mixing the positive electrode active material and the compound in a solid state and coating the surface of the positive electrode active material with the compound.
[0097] First, the step (1) of preparing a compound represented by the above chemical formula 1 may include a step of solid-state mixing of a lithium halide and a lithium metal halide (e.g., lithium metal fluoride or lithium metal oxyfluoride).
[0098] The above lithium halide may include LiCl, LiBr, LiI, or a combination thereof.
[0099] For example, the above lithium metal halide is Li a M 1 X 2 b-c O cIt can be displayed as, and X 2 is F, Cl, Br, I, or a combination thereof, and M 1 is B, Al, Ga, In, Ti, Zr, Hf, Fe, or a combination thereof, where 0.01≤a≤10, 0.01≤b≤10, and 0≤c
[0100] For example, the above Li a M 1 X 2 b-c O c 0 in lithium metal halides indicated by <c<b인 경우에는, 산소 공급 물질을 더 포함하여 고상 혼합할 수 있으며, 상기 산소 공급 물질은 산화 리튬(Li2O)일 수 있다.
[0101] For example, the above lithium metal fluoride is Li a M 1 F b It can be represented as, and the above M 1 is B, Al, Ga, In, Ti, Zr, Hf, Fe, or a combination thereof, and may be 0.01≤a≤10 and 0.01≤b≤10.
[0102] As a specific example, the lithium metal fluoride is Li3AlF6, Li2TiF6 , Li2ZrF6, Li3FeF6, Li2Zr 0.5 Ti 0.5 F6, Li3Al 0.5 Fe 0.5 F 6, Li3HfF6, Li2TiF 5.6 O 0.2, Or it may include a combination of these.
[0103] The solid-state mixing of the lithium halide and the lithium metal halide can be performed by any one of the mechanical milling selected from a ball mill, a vibratory mill, a turbomill, a mechanofusion, and a disc mill, and preferably by a ball mill or a vibratory mill.
[0104] For example, the mechanical milling can be performed at a rotational speed of 300 to 800 rpm. For example, the mechanical milling can be performed for 10 to 50 hours, and as a specific example, it can be performed for 7 to 18 hours at a rotational speed of 500 to 700 rpm, and as a most specific example, it can be performed for 9 to 11 hours at a rotational speed of 580 to 620 rpm.
[0105] The positive active material is coated with the compound represented by Chemical Formula 1 prepared above (Step (2)).
[0106] The above-mentioned positive active material is as described above, and a detailed explanation is omitted here.
[0107] In the step (2) of coating the compound on the surface of the positive electrode active material, the coating can be performed by any one of mechanical milling selected from a ball mill, a vibratory mill, a turbomill, a mechanofusion, and a disc mill, and preferably by a ball mill or a vibratory mill.
[0108] For example, the mechanical milling can be performed for 0.5 to 10 hours at a rotational speed of 100 to 800 rpm, for a specific example, for 0.5 to 3 hours at a rotational speed of 200 to 300 rpm, and for the most specific example, for 0.5 to 1 hour at a rotational speed of 180 to 230 rpm.
[0109] All-solid-state battery
[0110] Another embodiment provides an all-solid-state battery comprising: a positive electrode comprising the above-mentioned composite positive electrode active material; a negative electrode; and a solid electrolyte disposed between the positive electrode and the negative electrode.
[0111] When the aforementioned composite cathode active material is applied to an all-solid-state battery, an all-solid-state battery with excellent performance, such as charge / discharge characteristics and lifespan characteristics, can be realized.
[0112] An all-solid-state battery will be described below with reference to Fig. 1.
[0113] FIG. 1 is a cross-sectional view of an all-solid-state battery according to one embodiment. Referring to FIG. 1, the all-solid-state battery (100) may have a structure in which an electrode assembly is stacked, comprising a negative electrode (400) including a negative electrode current collector (401) and a negative electrode active material layer (403), a solid electrolyte layer (300), and a positive electrode (200) including a positive electrode active material layer (203) and a positive electrode current collector (201), and the assembly is housed in a case such as a pouch. The all-solid-state battery (100) may further include an elastic layer (500) on the outer side of at least one of the positive electrode (200) and the negative electrode (400). FIG. 1 shows a single electrode assembly including a negative electrode (400), a solid electrolyte layer (300), and a positive electrode (200), but an all-solid-state battery may be manufactured by stacking two or more electrode assemblies.
[0114] In addition, a device including an all-solid-state battery according to one embodiment may be any one selected from a communication device, a transportation device, and an energy storage device.
[0115] In addition, as an electric device including an all-solid-state battery according to one embodiment, the electric device may be one selected from an electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, and a power storage device.
[0116] The charging voltage of the all-solid-state battery according to one embodiment may be 4.2V or higher, for example, 4.5V or higher, 4.6V or higher, 4.8V or higher, or 5V or higher.
[0117] The discharge voltage of the all-solid-state battery according to one embodiment may be 3.5V or less, for example, 3.0V or less, 2.5V or less, or 2.3V or less.
[0118] An all-solid-state battery satisfying the above numerical ranges of charging and discharging voltages has the advantage of excellent charging and discharging characteristics and lifespan characteristics when operating at high voltage charging or low voltage discharging.
[0119] anode
[0120] The above positive electrode (200) may include a positive electrode current collector (201) and a positive electrode active material layer (203) located on the positive electrode current collector (201).
[0121] The above-described positive active material layer (203) includes the composite positive active material described above and may optionally further include a solid electrolyte.
[0122] In one embodiment, the solid electrolyte included in the positive active material layer (203) may include a halide-based solid electrolyte, a sulfide-based solid electrolyte, an oxide-based solid electrolyte, a hydride complex, or a combination thereof, and the types of solid electrolytes that may be included in the positive active material layer (203) will be described later in the solid electrolyte layer section.
[0123] For example, the solid electrolyte included in the positive electrode active material layer (203) may be a halide-based solid electrolyte, and when the composite positive electrode active material described above and the halide-based solid electrolyte are used in combination, the high voltage stability of the all-solid-state battery can be further improved.
[0124] For example, the weight ratio of the composite positive active material and the solid electrolyte included in the positive active material layer (203) may be 30:70 to 70:30, for example 40:60 to 60:40, or 45:55 to 55:45.
[0125] cathode
[0126] The above-mentioned cathode (400) may be a general cathode containing various cathode active materials such as carbon-based or silicon-based materials, or a cathode made of a metal such as lithium metal, or a precipitation-type cathode in which no cathode active material is present initially but lithium metal is precipitated to act as a cathode active material upon charging.
[0127] For example, the cathode (400) may include a cathode current collector (401) and a cathode active material layer (403) located on the cathode current collector (401). The cathode active material layer (403) may include a cathode active material and optionally include a solid electrolyte. The solid electrolyte that may be included in the cathode active material layer (203) will be described later in the solid electrolyte layer section.
[0128] The negative electrode active material may include a material capable of reversibly intercalating / deintercalating lithium ions, lithium metal, an alloy of lithium metal, a material capable of doping and dedoping lithium, or a transition metal oxide.
[0129] A material capable of reversibly intercalating / deintercalating lithium ions is a carbon-based negative electrode active material, which may include, for example, crystalline carbon, amorphous carbon, or a combination thereof. Examples of crystalline carbon include natural graphite, artificial graphite, or a combination thereof, and examples of amorphous carbon include soft carbon or hard carbon, mesophase pitch carbide, calcined coke, etc. The carbon-based negative electrode active material may be amorphous, plate-like, flake-like, spherical, or fibrous.
[0130] As the above lithium metal alloy, an alloy of a metal selected from the group consisting of lithium, Na, K, Rb, Cs, Fr, Be, Mg, Ca, Sr, Si, Sb, Pb, In, Zn, Ba, Ra, Ge, Al, and Sn may be used.
[0131] As a material capable of doping and undoping the above lithium, a Si-based negative electrode active material or a Sn-based negative electrode active material may be used, and the Si-based negative electrode active material may include silicon, a silicon-carbon composite, or SiO₂. x (0 <x<2), 실리콘 합금 등이 있으며, Sn계 음극 활물질로는 Sn, SnO2, 주석 합금 등을 들 수 있고, 이들 중 적어도 하나와 SiO2를 혼합하여 사용할 수도 있다. 일 예로 음극 활물질은 실리콘과 탄소의 복합체를 포함할 수도 있다.
[0132] solid electrolyte layer
[0133] The solid electrolyte layer (300) includes a solid electrolyte, and the solid electrolyte may include a sulfide-based solid electrolyte.
[0134] Sulfide-based solid electrolytes can be classified into crystalline solid electrolytes and non-crystalline solid electrolytes depending on the presence or absence of a crystalline structure. Li is an example of a crystalline solid electrolyte. 3.25 Ge 0.25 P 0.75 Thio-LISICON of S4, etc., Li 10 GeP2S 12 Representative examples include agrodiodite structures such as LGPS and Li6PS5Cl. Amorphous solid electrolytes can be classified into glass-based solid electrolytes and glass-ceramic-based solid electrolytes based on differences in heat treatment temperatures; examples of glass-based solid electrolytes include 30Li2S·26B2S3·44LiO, 63Li2S·36SiS2·1Li3PO4, and 57Li2S·38SiS2·5Li4SiO4, while examples of glass-ceramic-based solid electrolytes include Li 3.25 P 0.95 S4, Li7P3S 11 There are others.
[0135] Sulfide-based solid electrolytes may be classified into structures such as azirodite, binary structures such as Li2S-P2S5, and ternary structures such as Li2S-GeS2-P2S5.
[0136] The above sulfide-based solid electrolyte may be an azirodite-type sulfide-based solid electrolyte. Azirodite is one of the solid electrolytes that exhibits lithium ion conductivity while having the same structure as the ore Ag9GeS6. Li + Representative conductive Li-azirodites include Li7PS6 and Li6PS5X (X=Cl, Br, or I). Synthesis methods for azirodite-type sulfide-based solid electrolytes generally include mechanical milling, annealing after milling, solid sintering, and liquid-phase methods.
[0137] Li7PS6, an azyrodite type, has been reported to possess a cubic phase at high temperatures and an orthorhombic phase at low temperatures, with the cubic phase at high temperatures potentially exhibiting enhanced ionic conductivity. This compound can be stabilized by replacing sulfur with halogen anions. The substitution of halogen elements forms vacancies in the lithium site portions within the azyrodite unit cell, thereby improving lithium ion conductivity. Furthermore, due to the substitution of halogen ions, the cubic phase is stabilized even at room temperature; for example, Li6PS5Br and Li6PS5Cl are 10 -3 It can exhibit high ionic conductivity of S / cm or higher.
[0138] As an example, the above azirodite-type sulfide-based solid electrolyte is, for example, Li7PS5Br, Li5PS4Cl2, Li6PS5Cl, Li6PS5Br, Li6PS5I, Li7P2S8I, Li4PS4I, Li 9.54 Si 1.74 P 1.44 S 11.7 Cl 0.3 , Li7P 2.9 Mn 0.1 S10.7 I 0.3 , or a combination thereof may be included, but is not limited thereto.
[0139] For example, the above sulfide-based solid electrolyte is Li 7+x-y M x 4+ M 1-x 5+ S 6-y X y (M 4+ : Si, Ge, S or Sn; M 5+ :P, Sb; X: Cl, Br, I, 0 ≤ x ≤ 1, 0 ≤ y ≤ 2), Li 10+a [Ge b M 4+ 1-b ] 1+a P 2a S 12-c X c (M 4+ : Si, Sn; X: Cl, Br, I, 0 ≤ a ≤ 2, 0 ≤ b ≤ 1, 0 ≤ c ≤ 4), or a combination thereof may be included.
[0140] Sulfide-based solid electrolytes are in the form of particles, and the average particle size (D 50 The ) can be 5.0 μm or less, for example, 0.1 μm to 5.0 μm, 0.5 μm to 5.0 μm, 0.5 μm to 4.0 μm, 0.5 μm to 3.0 μm, 0.5 μm to 2.0 μm, or 0.5 μm to 1.0 μm. Such sulfide-based solid electrolytes can achieve high ionic conductivity and have excellent contact with the cathode active material and connectivity between solid electrolyte particles.
[0141] The solid electrolyte layer (300) may further include other solid electrolytes other than the aforementioned sulfide-based solid electrolyte, for example, an oxide-based solid electrolyte, a halide-based solid electrolyte, a hydride complex, or a combination thereof.
[0142] Oxide-based solid electrolytes are, for example, Li 1+xTi 2-x Al(PO4)3(LTAP)(0≤x≤4), Li 1+x+y Al x Ti 2-x Si y P 3-y O 12 (0 <x<2, 0≤y<3), BaTiO3, Pb(Zr,Ti)O3(PZT), Pb 1-x La x Zr 1-y Ti y O3(PLZT)(0≤x<1, 0≤y<1), PB(Mg3Nb 2 / 3 )O3-PbTiO3(PMN-PT), HfO2, SrTiO3, SnO2, CeO2, Na2O, MgO, NiO, CaO, BaO, ZnO, ZrO2, Y2O3, Al2O3, TiO2, SiO2, Lithium Phosphate (Li3PO4), Lithium Titanium Phosphate (Li x Ti y (PO4)3, 0 <x<2, 0<y<3), Li 1+x+y (Al,Ga) x (Ti,Ge) 2-x Si y P 3-y O 12 (0≤x≤1, 0≤y≤1), lithium lanthanum titanate (Li x La y TiO3, 0 <x<2, 0<y<3), Li2O, LiAlO2, Li2O-Al2O3-SiO2-P2O5-TiO2-GeO2세라믹스, 가넷형 세라믹스 Li 3+x La3M2O 12 (M=Te, Nb, or Zr, and x is an integer from 1 to 10), or may include a combination thereof.
[0143] A halide-based solid electrolyte contains a halogen element as a main component, and the ratio of the halogen element to all elements constituting the solid electrolyte may be 50 mol% or more, 70 mol% or more, 90 mol% or more, or 100 mol%.
[0144] Halide-based solid electrolytes may contain lithium elements, metal elements other than lithium, and halogen elements. Metal elements other than lithium may be, for example, Al, As, B, Bi, Ca, Cd, Co, Cr, Fe, Ga, Hf, In, Mg, Mn, Ni, Sb, Sc, Sn, Ta, Ti, Y, Zn, Zr, or combinations thereof. Halogen elements may be F, Cl, Br, I, or combinations thereof, and for example, Cl, Br, or combinations thereof.
[0145] For example, the above halide-based solid electrolyte may include one or more of the compounds represented by the following chemical formulas 3 to 6.
[0146] [Chemical Formula 3]
[0147] Li a3 M 4 O b3 X 3 c3
[0148] In the above chemical formula 3,
[0149] M 4 is Al, As, B, Bi, Ca, Cd, Co, Cr, Fe, Ga, Hf, In, Mg, Mn, Nb, Ni, Sb, Sc, Sn, Ta, Ti, Y, Yb, Zn, Zr, or a combination thereof, and
[0150] X 3 is F, Cl, Br, I, or a combination thereof, and
[0151] 1≤a3≤3, 0≤b3≤1, and 4≤c3≤6.
[0152] [Chemical Formula 4]
[0153] Li2O-M 5 X 3 c4
[0154] In the above chemical formula 4,
[0155] M 5is Al, As, B, Bi, Ca, Cd, Co, Cr, Fe, Ga, Hf, In, Mg, Mn, Nb, Ni, Sb, Sc, Sn, Ta, Ti, Y, Yb, Zn, Zr, or a combination thereof, and
[0156] X 3 is F, Cl, Br, I or a combination thereof, and 4≤c4≤6.
[0157] [Chemical Formula 5]
[0158] M 6 O c5 -Li a5 M 7 X 3 b5-d5 X 4 d5
[0159] In the above chemical formula 5,
[0160] M 6 and M 7 are identical or different, and each independently is Mg, Ca, Zn, Cd, Cu, Sc, Y, B, Al, Ga, In, Ln, La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Yb, Lu, Ti, Zr, Hf, Nb, Ta, Mo, W, Sb, Si, Ge, Sn, V, Cr, Mn, Fe, Co, Ni, or a combination thereof, and
[0161] X 3 and X 4 are distinct from each other, and each is independently Cl, Br, F, or I, and
[0162] 0.01≤a5≤10, 0.01≤b5≤10, 0.01≤c5≤10, and 0.01≤d5≤4.
[0163] [Chemical Formula 6]
[0164] Li a6 M 8 X 3 b6-d6 X 4 d6
[0165] In the above chemical formula 6,
[0166] M 8 It may include Mg, Ca, Zn, Cd, Cu, Sc, Y, B, Al, Ga, In, Ln, La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Yb, Lu, Ti, Zr, Hf, Nb, Ta, Mo, W, Sb, Si, Ge, Sn, V, Cr, Mn, Fe, Co, Ni, or combinations thereof, and
[0167] X is Cl, Br, F, or I, and
[0168] X 3 and X 4 are distinct from each other, and each is independently Cl, Br, F, or I, and
[0169] 0.01≤a6≤10, 0.01≤b6≤10, 0.01≤c6≤10, and 0.01≤d6≤4.
[0170] For example, the above halide-based solid electrolyte is Li2ZrCl6, Li 2.7 Y 0.7 Zr 0.3 Cl6, Li 2.5 Y 0.5 Zr 0.5 Cl6, Li 2.5 In 0.5 Zr 0.5 Cl6, Li2In 0.5 Zr 0.5 Cl6, Li3YBr6, Li3YCl6, Li3YBr2Cl4, Li3YbCl6, Li 2.6 Hf 0.4 Yb 0.6 It may include Cl6, LiAlCl4, LiNbOCl4, LiTaOCl4, or a combination thereof.
[0171] For example, the above halide-based solid electrolyte is Li2ZrCl6, Li 2.7 Y 0.7 Zr 0.3 Cl6, Li 2.5 Y 0.5 Zr0.5 Cl6, Li 2.5 In 0.5 Zr 0.5 Cl6, Li2In 0.5 Zr 0.5 Cl6, Li3YBr6, Li3YCl6, Li3YBr2Cl4, Li3YbCl6, Li 2.6 Hf 0.4 Yb 0.6 Cl6, LiAlCl4, LiNbOCl4, LiTaOCl4, Li2O-TaCl5, MgO-Li2ZrCl 6, Al2O3-3Li2ZrCl 6, Al2O3-2Li3YCl 6, Al2O3-3Li2ZrCl 6, 3ZrO2-4Li3YCl 6, ZrO2-2Li2ZrCl 6, ZrO2-2Li2ZrCl5F, SiO2-2Li2ZrCl 6, It may include SnO2-2Li2ZrCl6, or a combination thereof.
[0172] Complex hydrides are, for example, metal cations (M) and M'H n Composed of complex anions of the form (MM'H n ) may be. The metal cation (M) may be, for example, Li, Na, K, Mg, Sc, Cu, Zn, Zr, or Hf, and the complex anion may be [BH4] - , [NH2] - , [AlH4] - , [NH] 2- , [AlH6] 3- , or [NiH4] 4- It may be. For hydride complexes, refer to the literature "M. Matsuo, S.-i. Orimo, Adv. Energy Mater. 2011, 1, 161".
[0174] Various embodiments and experimental examples of the present invention are described in detail below. However, the following embodiments are merely some embodiments of the present invention and should not be interpreted as limiting the present invention to the following embodiments.
[0175] (Synthesization Example: Preparation of Composite Cathode Active Material)
[0176] Synthesis Example 1
[0177] First, LiCl and Li3AlF6 are weighed in a molar ratio of 1:3, and LiCl-Li3AlF6 is synthesized by mechanically milling a 50 ml ZrO2 vial containing 15 ZrO2 balls (ф = 10 mm) in a Pulverisette 7 PL (Fritsch GmbH) in an Ar atmosphere at 600 rpm for 10 hours.
[0178] Next, LiNi 0.5 Mn 1.5 The above LiCl-Li3AlF6 is weighed to contain 5 parts by weight per 100 parts by weight of O4, and mechanically milled at 200 rpm for 1 hour under the same conditions as above to produce LiNi 0.5 Mn 1.5 A composite cathode active material is prepared by coating LiCl-Li3AlF6 on the surface of O4.
[0179] Synthesis Example 2
[0180] LiNi 0.5 Mn 1.5 A composite cathode active material is prepared in the same manner as in Synthesis Example 1, except that the above LiCl-Li3AlF6 is weighed and prepared to contain 10 parts by weight per 100 parts by weight of O4 (polycrystalline, average particle size 15 μm).
[0181] Synthesis Example 3
[0182] LiNi 0.5 Mn 1.5A composite cathode active material is prepared in the same manner as in Synthesis Example 1, except that the above LiCl-Li3AlF6 is weighed and prepared to contain 15 parts by weight per 100 parts by weight of O4.
[0183] Synthesis Example 4
[0184] First, LiCl and Li2TiF6 are weighed in a molar ratio of 1:4, and LiCl-Li2TiF6 is synthesized by mechanically milling a 50 ml ZrO2 vial containing 15 ZrO2 balls (ф = 10 mm) in a Pulverisette 7 PL (Fritsch GmbH) in an Ar atmosphere at 600 rpm for 10 hours.
[0185] Next, LiNi 0.5 Mn 1.5 The above LiCl-Li2TiF6 is weighed to contain 10 parts by weight per 100 parts by weight of O4, and mechanically milled at 200 rpm for 1 hour under the same conditions as above to produce LiNi 0.5 Mn 1.5 A composite cathode active material is prepared by coating LiCl-Li2TiF6 on the surface of O4.
[0186] Synthesis Example 5
[0187] A composite cathode active material is prepared in the same manner as in Synthesis Example 1, except that LiCl-Li3AlF6 is synthesized as described in Synthesis Example 1, and then LiCl-Li3AlF6 is weighed to be included in 10 parts by weight per 100 parts by weight of LiCoMnO4, and then coated on the surface of LiCoMnO4 (single crystal, average particle size 7.5 μm) by mechanical milling.
[0188] Synthesis Example 6
[0189] First, LiCl and Li2TiF6 were weighed to be contained in a molar ratio of 1:4, and Li2O was additionally mixed. Then, the mixture was mechanically milled in an Ar atmosphere using a Pulverisette 7 PL (Fritsch GmbH) in a 50 ml ZrO2 vial containing 15 ZrO2 balls (ф = 10 mm) at 600 rpm for 10 hours to produce the LiCl-Li2TiF6 5.6 O 0.2 Synthesizes.
[0190] Next, LiNi 0.5 Mn 1.5 The above LiCl-Li2TiF with respect to 4100 parts by weight of O4 5.6 O 0.2 Weighed so as to be included in an amount of 10 parts by weight, and mechanically milled at 200 rpm for 1 hour under the same conditions as above to produce LiNi 0.5 Mn 1.5 LiCl-Li2TiF on the surface of O4 5.6 O 0.2 This coated composite cathode active material is manufactured.
[0191] Comparative Synthesis Example 1
[0192] LiNi 0.5 Mn 1.5 Li3AlF6 was weighed to contain 10 parts by weight per 100 parts by weight of O4, and mechanically milled under the same conditions as described above in Synthesis Example 1 to obtain LiNi 0.5 Mn 1.5 A composite cathode active material is prepared by coating Li3AlF6 on the surface of O4.
[0193] Comparative Synthesis Example 2
[0194] LiNi 0.5 Mn 1.5 Li3YCl6 was weighed to contain 10 parts by weight per 100 parts by weight of O4, and LiNi was mechanically milled under the same conditions as described above in Synthesis Example 1. 0.5 Mn 1.5 A composite cathode active material is prepared by coating Li3YCl6 on the surface of O4.
[0195] Comparative Synthesis Example 3
[0196] LiNi 0.5 Mn 1.5 A precursor mixture is prepared by adding lithium ethoxide and niobium ethoxide to ethanol and stirring so that LiNbO3 is contained in an amount of 5 parts by weight per 100 parts by weight of O4, and after evaporating the solvent (ethanol) for 30 minutes using a rotary evaporator, it is heat-treated for 1 hour to produce LiNi 0.5 Mn 1.5 A composite cathode active material is prepared by coating LiNbO3 on the surface of O4.
[0197] Comparative Synthesis Example 4
[0198] LiNi 0.5 Mn 1.5 Li2TiF6 was weighed to contain 10 parts by weight per 100 parts by weight of O4, and LiNi was mechanically milled under the same conditions as described above in Synthesis Example 1. 0.5 Mn 1.5 A composite cathode active material is prepared by coating Li2TiF6 on the surface of O4.
[0199] Comparative Synthesis Example 5
[0200] LiNi 0.5 Mn 1.5 Li per 4100 parts by weight of O 2.25 TiF 5.75 O 0.25 Weighed so as to be included in an amount of 10 parts by weight, and mechanically milled under the same conditions as described above in Synthesis Example 1 to obtain LiNi 0.5 Mn 1.5 Li on the surface of O4 2.25 TiF 5.75 O 0.25 This coated composite cathode active material is manufactured.
[0201] Comparative Synthesis Example 6
[0202] LiNi 0.5 Mn 1.5 Li per 4100 parts by weight of O 2.5 TiF 5.5 O0.5 Weighed so as to be included in an amount of 10 parts by weight, and mechanically milled under the same conditions as described above in Synthesis Example 1 to obtain LiNi 0.5 Mn 1.5 Li on the surface of O4 2.5 TiF 5.5 O 0.5 This coated composite cathode active material is manufactured.
[0203] Comparative Synthesis Example 7
[0204] LiNi 0.5 Mn 1.5 Li per 4100 parts by weight of O 2.75 TiF 5.25 O 0.75 Weighed so as to be included in an amount of 10 parts by weight, and mechanically milled under the same conditions as described above in Synthesis Example 1 to obtain LiNi 0.5 Mn 1.5 Li on the surface of O4 2.75 TiF 5.25 O 0.75 This coated composite cathode active material is manufactured.
[0205] Composite cathode active material positive electrode active material coating layer furtherance Weight of the coating layer per 100 weight parts of the positive electrode active material Synthesis Example 1 LiNi 0.5 Mn 1.5 O4 LiCl-Li3AlF6 5 parts by weight Synthesis Example 2 LiNi 0.5 Mn 1.5 O4 LiCl-Li3AlF6 10 parts by weight Synthesis Example 3 LiNi 0.5 Mn 1.5 O4 LiCl-Li3AlF6 15 parts by weight Synthesis Example 4 LiNi 0.5 Mn 1.5 O4 LiCl-Li2TiF6 10 parts by weight Synthesis Example 5 LiCoMnO4 LiCl-Li3AlF6 10 parts by weight Synthesis Example 6 LiNi 0.5 Mn 1.5 O4 LiCl-Li2TiF 5.6 O 0.2 10 parts by weight Comparative Synthesis Example 1 LiNi 0.5 Mn 1.5 O4 Li3AlF6 10 parts by weight Comparative Synthesis Example 2 LiNi 0.5 Mn 1.5 O4 Li3YCl6 10 parts by weight Comparative Synthesis Example 3 LiNi 0.5 Mn 1.5 O4 LiNbO3 5 parts by weight Comparative Synthesis Example 4 LiNi 0.5 Mn 1.5 O4 Li2TiF6 10 parts by weight Comparative Synthesis Example 5 LiNi 0.5 Mn 1.5 O4 Read 2.25 TiF 5.75 Oh 0.25 10 parts by weight Comparative Synthesis Example 6 LiNi 0.5 Mn 1.5 O4 Read 2.5 TiF 5.5 Oh 0.5 10 parts by weight Comparative Synthesis Example 7 LiNi 0.5 Mn 1.5 O4 Read 2.75 TiF 5.25 Oh 0.75 10 parts by weight
[0206] Evaluation Example 1: XRD Evaluation
[0207] The XRD of LiCl-Li3AlF6 and Li3AlF6 used as coating materials in Synthesis Example 1 and Comparative Synthesis Example 1, and LiCl-Li2TiF6 and Li2TiF6 used as coating materials in Synthesis Example 4 and Comparative Synthesis Example 4, is analyzed by the following method.
[0208] First, the sample is sealed using a Be cover inside a glove box in an argon atmosphere. An X-ray diffraction analyzer (Miniflex-600) manufactured by Rigaku is used as the X-ray diffraction measuring device, and Cu Kα is used as the X-ray source. Measurements are taken over a measurement range of 10° to 80° with a step-size of 0.02° and a speed of 2.0 deg / min.
[0209] The measurement results are shown as graphs in Figures 2 and 3. For reference, the enlarged portion on the right in Figure 2 indicates that no XRD peak shifting of Li3AlF6 occurred during the process of complexation with LiCl in Synthesis Example 1, and the enlarged portion on the right in Figure 3 indicates that no XRD peak shifting of Li2TiF6 occurred during the process of complexation with LiCl in Synthesis Example 4.
[0210] Referring to Fig. 2, it can be seen that peaks due to both LiCl and Li3AlF6 are observed in the coating material used in Synthesis Example 1, whereas only peaks due to Li3AlF6 are observed in the coating material used in Comparative Synthesis Example 1. Referring to Fig. 3, it can be seen that peaks due to both LiCl and Li2TiF6 are observed in the coating material used in Synthesis Example 4, whereas only peaks due to Li2TiF6 are observed in the coating material used in Comparative Synthesis Example 4.
[0211] Evaluation Example 2: Ionic Conductivity Evaluation
[0212] In addition, the lithium ion conductivity of LiCl-Li3AlF6 and Li3AlF6 used as coating materials in Synthesis Example 1 and Comparative Synthesis Example 1, and the lithium ion conductivity of LiCl-Li2TiF6 and Li2TiF6 used as coating materials in Synthesis Example 4 and Comparative Synthesis Example 4 are measured by the following impedance method.
[0213] First, an appropriate amount of sample is weighed in a glove box under an argon atmosphere and placed into a polyetheretherketone tube (PEEK tube, inner diameter 13 mm, outer diameter 32 mm, height 10 mm), and the upper and lower ends of the polyetheretherketone tube are fitted into a powder molding jig containing Ti. Next, a pellet of a diameter of 13 mm and any thickness is formed by pressing with a molding pressure of about 370 MPa using a single-screw press. After that, the obtained pellet is placed in a closed electrochemical cell capable of maintaining an argon atmosphere.
[0214] For the measurement, a Gain / Gain-Phase Analyzer (SP-300) manufactured by Biologics is used as the Frequency Response Analyzer (FRA), and a small environmental tester is used as the constant temperature device. Measurement is initiated from the high-frequency region under conditions of an AC voltage of 10 mV to 100 mV, a frequency range of 10 Hz to 7 MHz, and a temperature of 30℃.
[0215] The measurement results are shown as graphs in Figures 4 and 5.
[0216] Referring to Fig. 4, it can be seen that the lithium metal fluoride compound (LiCl-Li3AlF6) combined with the lithium chloride compound used in Synthesis Example 1 has superior lithium ion conductivity compared to the lithium metal fluoride compound (Li3AlF6) used in Comparative Synthesis Example 1.
[0217] Referring to Fig. 5, it can be seen that the lithium metal fluoride compound (LiCl-Li2TiF6) combined with the lithium chloride compound used in Synthesis Example 4 has superior lithium ion conductivity compared to the lithium metal fluoride compound (Li2TiF6) used in Comparative Synthesis Example 4.
[0218] Also, LiCl-Li2TiF used as a coating material in Synthesis Example 6 5.6 O 0.2 , Li used as a coating material in Comparative Synthesis Example 5 2.25 TiF 5.75 O 0.25 , Li used as a coating material in Comparative Synthesis Example 6 2.5 TiF 5.5 O 0.5, and Li used as a coating material in Comparative Synthesis Example 7 2.75 TiF 5.25 O 0.75 The lithium ion conductivity of is measured by the same impedance method as described above.
[0219] The results of measuring the ion conductivity of the coating materials of Synthesis Example 4, Synthesis Example 6, and Comparative Synthesis Examples 4 to 7 are shown in Table 2 below.
[0220] furtherance Ionic conductivity (S cm) -1 , 30 o C) Comparative Synthesis Example 4 Li2TiF6 5.8 x 10 -8 Synthesis Example 4 LiCl-Li2TiF6 1.7 x 10 -5 Comparative Synthesis Example 5 Read 2.25 TiF 5.75 Oh 0.25 1.3 x 10 -6 Comparative Synthesis Example 6 Read 2.5 TiF 5.5 Oh 0.5 4.0 x 10 -6 Comparative Synthesis Example 7 Read 2.75 TiF 5.25 Oh 0.75 5.0 x 10 -6 Synthesis Example 6 LiCl-Li2TiF 5.6 O 0.2 1.1 x 10 -5
[0221] Referring to Table 2, it can be seen that the ionic conductivity of the coating material in Synthesis Example 4, which uses LiCl-Li2TiF6 as the coating material, is significantly higher than that in Comparative Synthesis Example 4, which uses Li2TiF6 alone as the coating material. In addition, when comparing Comparative Synthesis Example 4, which uses Li2TiF6 as the coating material, with Comparative Synthesis Examples 5 to 7, which use a coating material in which some of the F of Li2TiF6 is substituted with O, it can be seen that the ionic conductivity of the coating material used in Comparative Synthesis Examples 5 to 7 is excellent.
[0222] In addition, when comparing Comparative Synthesis Examples 5 to 7 with Synthesis Example 6, it can be confirmed that Synthesis Example 6, which contains lithium chloride, has a higher ionic conductivity.
[0223] Evaluation Example 3: Electrochemical Stability Evaluation
[0224] The electrochemical stability of the coating material is evaluated through cyclic voltammetry performed in a voltage range of 3 V to 5 V.
[0225] LiCl-Li3AlF6 and Li3AlF6 used as coating materials in Synthesis Example 1, Comparative Synthesis Example 1, and Comparative Synthesis Example 2 6, The results of the cyclic voltammetry evaluation for Li3YCl6 are shown in Fig. 6.
[0226] Referring to Fig. 6, it can be seen that in the case of the coating material of Comparative Synthesis Example 2, which is a chloride-based compound, the electrochemical stability is significantly reduced after 4 V.
[0227] On the other hand, in the case of the coating material of Synthesis Example 1, in which a chloride compound is combined with a fluoride compound, it can be confirmed that the electrochemical stability is excellent after 4 V.
[0228] Evaluation Example 4: SEM Analysis and Elemental Mapping
[0229] Figure 7 is an image of the composite cathode active material prepared in Synthesis Example 1 observed using a Scanning Electron Microscope (SEM).
[0230] FIG. 8 is an image of (a) the composite cathode active material prepared in Synthesis Example 1 analyzed by SEM-EDS (Energy Dispersive Spectrometer), (b) an image of Al mapping, (c) an image of Ni mapping, and (d) an image of Al and Ni mapping.
[0231] Referring to Fig. 7, LiNi 0.5 Mn 1.5 It can be observed that a coating material (LiCl-Li3AlF6) was formed on the O4 surface.
[0232] Also, referring to Fig. 8(a), the relatively dark areas are LiNi 0.5 Mn 1.5 It is O4, and the relatively bright areas correspond to the coated material.
[0233] Referring to Figures 8(b) to 8(d), the SEM-EDS elemental analysis results confirm that Al is distributed in the coated material.
[0234] Evaluation Example 5: XPS Analysis
[0235] X-ray photoelectron spectroscopy (XPS) analysis was performed on the composite cathode active material prepared in Synthesis Example 2, and the results are shown in Fig. 9.
[0236] In Fig. 9, (a) is the XPS graph of LiCl-Li3AlF6, and (b) LiNi0.5 Mn 1.5 This is an XPS graph of a composite cathode active material (Synthesis Example 2) coated with LiCl-Li3AlF6 on O4, and (c) LiNi 0.5 Mn 1.5 This is the XPS graph of O4.
[0237] Referring to Fig. 9, it can be confirmed that the composite cathode active material of Synthesis Example 2 contains all peaks representing bonding within the LiCl-Li3AlF6 structure.
[0238] (Example: Manufacture of an all-solid-state battery)
[0239] Examples 1 to 3
[0240] A cathode is prepared by mixing 48.5 wt% of each composite cathode active material prepared in Synthesis Examples 1 to 3 described above, 48.5 wt% of a solid electrolyte (Li3YCl6), and 3 wt% of a conductive material (Super-C).
[0241] Next, a solid electrolyte layer containing a Li6PS5Cl solid electrolyte and a cathode containing a Li-In cathode active material are prepared.
[0242] After stacking the above positive electrode (30 μm), solid electrolyte layer (600 μm), and negative electrode (100 μm), pressurize to manufacture an all-solid-state battery according to Examples 1 to 5.
[0243] Examples 4 to 5
[0244] A cathode is formed by mixing 48.5 wt% of each composite cathode active material prepared in Synthesis Examples 4 to 5 described above, 48.5 wt% of a solid electrolyte (ZrO2-2Li2ZrCl5F), and 3 wt% of a conductive material (Super-C).
[0245] Next, a solid electrolyte layer containing a Li6PS5Cl solid electrolyte and a cathode containing a Li-In cathode active material are prepared.
[0246] After stacking the above positive electrode (30 μm), solid electrolyte layer (600 μm), and negative electrode (100 μm), pressurize to manufacture an all-solid-state battery according to Examples 1 to 5.
[0247] Comparative Examples 1 to 3
[0248] An all-solid-state battery is manufactured in the same manner as Examples 1 to 5 above, except that it is manufactured using the composite cathode active material prepared in Comparative Synthesis Examples 1 to 3 described above.
[0250] Evaluation Example 6: Evaluation of Charge / Discharge Characteristics and Lifetime Characteristics
[0251] The initial charge-discharge characteristics of the all-solid-state batteries prepared in Examples 1, 2, and 3 were evaluated by repeating charging to 5.0V and discharging to 3.0V at rates of 0.1C, 0.2C, 0.5C, 1C, and 2C in an environment of 30°C, as shown in FIGS. 10 to 12. In addition, the discharge capacity after repeating the charge-discharge 25 times was measured and is shown in FIG. 19.
[0252] In addition, the initial charge-discharge characteristics of the all-solid-state battery prepared in Example 2 were evaluated by charging it to 5.0V at a constant current in an environment of 60°C and then discharging it to 2.3V at a rate of 0.1C, as shown in FIG. 13.
[0253] Referring to FIGS. 10 to 12, the all-solid-state batteries of Examples 1 to 3, which include a composite positive electrode active material according to one embodiment, exhibit excellent charge-discharge characteristics, and in particular, it can be confirmed that the charge-discharge characteristics of Example 2 are the best.
[0254] Referring to FIG. 13, it can be seen that the all-solid-state battery of Example 2, which includes a composite cathode active material according to one embodiment, has excellent charge-discharge characteristics even when operated with the discharge voltage lowered to 2.3V.
[0255] Referring to FIG. 19, it can be seen that the all-solid-state batteries of Examples 1 to 3 have excellent rate capability characteristics, and in particular, the all-solid-state battery according to Example 2 also has excellent capacity recovery characteristics.
[0256] For the all-solid-state batteries prepared in Example 2 and Comparative Example 1, the initial charge-discharge characteristics were evaluated by charging to 5.0V at a constant current in an environment of 30°C and then discharging to 3.0V at a rate of 0.1C, as shown in FIG. 14. In addition, the discharge capacity after repeating the charge-discharge cycle 150 times was measured and is shown in FIG. 20.
[0257] Referring to FIG. 14, it can be seen that when charging at high voltage, the all-solid-state battery according to Example 2 has a high initial discharge capacity, whereas the all-solid-state battery according to Comparative Example 1 has a low initial discharge capacity.
[0258] Referring to FIG. 20, the capacity retention rate according to the cycle is much better in the case of the all-solid-state battery according to Example 2, and it can be confirmed that the rate capability is superior to that of the all-solid-state battery according to Comparative Example 1.
[0259] For the all-solid-state battery according to Comparative Example 2, initial charge-discharge characteristics were evaluated by repeatedly charging to 5.0V and discharging to 3.0V at rates of 0.1C, 0.2C, 0.5C, 1C, and 2C in an environment of 30℃, and are shown in FIG. 15. . In addition, the discharge capacity after repeating the above charge and discharge 25 times is measured and shown in FIG. 21 together with the results of Example 2.
[0260] Referring to FIG. 15 and FIG. 21, it can be seen that the all-solid-state battery according to Comparative Example 2 has a very low initial discharge capacity and significantly lower rate capability compared to the all-solid-state battery according to Example 2.
[0261] For Comparative Example 3, the initial charge-discharge characteristics were evaluated by repeating charging to 5.0V and discharging to 3.0V at rates of 0.1C, 0.2C, 0.5C, 1C, and 2C in an environment of 30℃, and are shown in FIG. 16. In addition, the discharge capacity after repeating the charge-discharge 25 times was measured and is shown in FIG. 22 together with the results of Example 1.
[0262] Referring to FIGS. 16 and FIGS. 22, it can be seen that the all-solid-state battery according to Comparative Example 3 has a very low initial discharge capacity and significantly lower rate capability compared to the all-solid-state battery according to Example 1.
[0263] For Example 4, initial charge-discharge characteristics were evaluated by repeating charging to 5.0V and discharging to 3.0V at rates of 0.1C, 0.2C, 0.5C, 1C, and 2C in an environment of 30℃, as shown in FIG. 17. In addition, the discharge capacity after repeating the charge-discharge 25 times was measured and is shown in FIG. 23.
[0264] For Example 5, initial charge-discharge characteristics were evaluated by repeating charging to 5.5V and discharging to 3.0V at rates of 0.1C, 0.2C, 0.5C, 1C, and 2C in an environment of 60℃, as shown in FIG. 18. In addition, the discharge capacity after repeating the charge-discharge 25 times was measured and is shown in FIG. 24.
[0265] Referring to FIGS. 17 to 18 and FIGS. 23 to 24, it can be seen that in the case of Example 4 and Example 5, the initial charge / discharge characteristics are equivalent to those of Example 1 to 3, and the capacity retention rate and capacity recovery rate are also equivalent to those of Example 1 to 3.
[0267] Although the embodiments have been described in detail above, the scope of the rights is not limited thereto, and various modifications and improvements by those skilled in the art using the basic concepts defined in the following claims are also included within the scope of the rights. Explanation of the symbols
[0269] 100: All-solid-state battery 200: Anode 201: Positive current collector 203: Positive active material layer 300: Solid electrolyte layer 400: Cathode 401: Cathode current collector 403: Cathode active material layer 500: Elastic layer
Claims
Claim 1 A composite positive active material comprising: a positive active material; and a coating layer located on the surface of the positive active material and comprising a compound represented by the following chemical formula 1, wherein, with respect to 100 parts by weight of the positive active material, the coating layer is included in an amount of 5 to 15 parts by weight: [Chemical Formula 1]LiX 1 -Li a M 1 X 2 b-c O c In the above chemical formula 1, X 1 and X 2 are each independently F, Cl, Br, I, or a combination thereof, and M 1 is B, Al, Ga, In, Ti, Zr, Hf, Fe, or a combination thereof, where 0.01≤a≤10, 0.01≤b≤10, and 0≤c <b이다. Claim 2 In claim 1, the compound represented by Chemical Formula 1 comprises a compound represented by the following Chemical Formula 1A, a composite cathode active material: [Chemical Formula 1A]LiCl-Li a M 1 F b-c O c In the above chemical formula 1A, M 1 is B, Al, Ga, In, Ti, Zr, Hf, Fe, or a combination thereof, where 0.01≤a≤10, 0.01≤b≤10, and 0≤c <b 이다. Claim 3 In claim 2, the compound represented by Chemical Formula 1A comprises a compound represented by Chemical Formula 1A-1, a compound represented by Chemical Formula 1A-2, or a combination thereof, in a composite cathode active material: [Chemical Formula 1A-1]LiCl-Li a AlF b [Chemical Formula 1A-2]LiCl-Li a TiF b In the above chemical formulas 1A-1 and 1A-2, 0.01≤a≤10 and 0.01≤b≤10. Claim 4 In claim 1, the compound represented by Chemical Formula 1 comprises a compound represented by Chemical Formula 1B-1, a compound represented by Chemical Formula 1B-2, or a combination thereof, in a composite cathode active material: [Chemical Formula 1B-1]LiF 1-x1 Cl x1 -Li a TiF b In the above chemical formula 1B-1, 0.01≤a≤10, 0.01≤b≤10, and 0 <x1<1이고,[화학식 1B-2]LiCl-Li a TiF b1-x2 Cl x2 In the above chemical formula 1B-2, 0.01≤a≤10, 0.01≤b1≤10, and 0 <x2<b1이다. Claim 5 In claim 1, the compound represented by Chemical Formula 1 comprises a compound represented by the following Chemical Formula 1C, a composite cathode active material: [Chemical Formula 1C]LiCl-Li a TiF b2-x3-c1 Cl x3 O c1 In the above chemical formula 1C, 0.01≤a≤10, 0.01≤b2≤10, and 0≤x3 <b2, 0<c1<b2 이다. Claim 6 In claim 1, the compound represented by the above chemical formula 1 is LiCl-Li3AlF6, LiCl-Li2TiF6 , LiCl-Li2ZrF6, LiCl-Li3FeF6, LiCl-Li2Zr 0.5 Ti 0.5 F6, LiCl-Li3Al 0.5 Fe 0.5 F6, LiCl-Li3HfF6, LiCl-Li2TiF 5.6 O 0.2, A composite positive electrode active material comprising a combination thereof. Claim 7 In claim 1, LiX in the compound represented by the above chemical formula 1 1 and Li a M 1 X 2 b-c O c A composite cathode active material included in a molar ratio of 1:1 to 1:
9. Claim 8 In claim 1, the anode active material comprises a compound represented by the following chemical formula 2A, a composite anode active material: [Chemical Formula 2A]Li d M 2 e Mn 2-e O 4-f A f In the above chemical formula 2A, M 2 is Al, Ni, Co, Mn, Zn, Cr, Mg, Sr, V, Ca, Ti, Y, Zr, Nb, Mo, Hf, Ta, W, Na, Sn, rare earth elements, or a combination thereof, A is F, Cl, Br, or I, and 1≤d≤2, 0≤e<2, and 0≤f<4. Claim 9 In claim 8, the above-mentioned positive active material is a composite positive active material comprising a compound represented by the following chemical formula 2B: [Chemical Formula 2B]Li d1 Ni e1 M 3 e2 Mn e3 O 2-f1 A f1 In the above chemical formula 2B, M 3 is Al, Co, Mn, Zn, Cr, Fe, Mg, Sr, V, Ca, Ti, Y, Zr, Nb, Mo, Hf, Ta, W, Na, Sn, rare earth elements, or a combination thereof, and A is F, Cl, Br, I, S, P, or a combination thereof, and 1≤d1≤2, 0<e1≤1, 0<e2≤1, 0<e3≤1, and 0≤f1<2. Claim 10 delete Claim 11 In claim 1, the lithium ion conductivity of the compound represented by Chemical Formula 1 is 1.0 x 10⁻⁶ -6 Composite cathode active material with S / cm or higher. Claim 12 Anode comprising a positive current collector; and a positive active material layer located on the positive current collector, wherein the positive active material layer comprises a positive active material and a coating layer located on the surface of the positive active material and comprising a compound represented by the following chemical formula 1, wherein the coating layer is included in an amount of 5 to 15 parts by weight per 100 parts by weight of the positive active material, the anode comprising a composite positive active material: [Chemical Formula 1]LiX 1 -Li a M 1 X 2 b-c O c In the above chemical formula 1, X 1 and X 2 are each independently F, Cl, Br, I, or a combination thereof, and M 1 is B, Al, Ga, In, Ti, Zr, Hf, Fe, or a combination thereof, where 0.01≤a≤10, 0.01≤b≤10, and 0≤c <b이다. Claim 13 In claim 12, the anode comprising the compound represented by Chemical Formula 1, wherein the compound represented by Chemical Formula 1 comprises the compound represented by the following Chemical Formula 1A: [Chemical Formula 1A]LiCl-Li a M 1 F b-c O c In the above chemical formula 1A, M 1 is B, Al, Ga, In, Ti, Zr, Hf, Fe, or a combination thereof, where 0.01≤a≤10, 0.01≤b≤10, and 0≤c <b 이다. Claim 14 In claim 13, the compound represented by the above formula 1A comprises the compound represented by the following formula 1A-1, the compound represented by the formula 1A-2, or a combination thereof, anode: [Formula 1A-1]LiCl-Li a AlF b [Chemical Formula 1A-2]LiCl-Li a TiF b In the above chemical formulas 1A-1 and 1A-2, 0.01≤a≤10 and 0.01≤b≤10. Claim 15 In claim 12, the compound represented by Chemical Formula 1 comprises a compound represented by Chemical Formula 1B-1, a compound represented by Chemical Formula 1B-2, or a combination thereof, anode: [Chemical Formula 1B-1]LiF 1-x1 Cl x1 -Li a TiF b In the above chemical formula 1B-1, 0.01≤a≤10, 0.01≤b≤10, and 0 <x1<1이고,[화학식 1B-2]LiCl-Li a TiF b1-x2 Cl x2 In the above chemical formula 1B-2, 0.01≤a≤10, 0.01≤b1≤10, and 0 <x2<b1이다. Claim 16 In claim 12, the anode comprising the compound represented by the above chemical formula 1, wherein the compound represented by the following chemical formula 1C comprises the compound represented by the following chemical formula 1C: [Chemical Formula 1C]LiCl-Li a TiF b2-x3-c1 Cl x3 O c1 In the above chemical formula 1C, 0.01≤a≤10, 0.01≤b2≤10, and 0≤x3 <b2, 0<c1<b2 이다. Claim 17 In claim 12, the compound represented by the above chemical formula 1 is LiCl-Li3AlF6, LiCl-Li2TiF6 , LiCl-Li2ZrF6, LiCl-Li3FeF6, LiCl-Li2Zr 0.5 Ti 0.5 F6, LiCl-Li3Al 0.5 Fe 0.5 F6, LiCl-Li3HfF6, LiCl-Li2TiF 5.6 O 0.2, or a positive electrode comprising a combination thereof. Claim 18 In claim 12, in the compound represented by the above chemical formula 1, LiX 1 and Li a M 1 X 2 b-c O c The anode is included in a molar ratio of 1:1 to 1:
9. Claim 19 In claim 12, the anode active material comprises a compound represented by the following chemical formula 2A, anode: [Chemical Formula 2A]Li d M 2 e Mn 2-e O 4-f A f In the above chemical formula 2A, M 2 is Al, Ni, Co, Mn, Zn, Cr, Mg, Sr, V, Ca, Ti, Y, Zr, Nb, Mo, Hf, Ta, W, Na, Sn, rare earth elements, or a combination thereof, A is F, Cl, Br, or I, and 1≤d≤2, 0≤e<2, and 0≤f<4. Claim 20 In claim 19, the anode active material comprises a compound represented by the following chemical formula 2B, anode: [Chemical Formula 2B]Li d1 Ni e1 M 3 e2 Mn e3 O 2-f1 A f1 In the above chemical formula 2B, M 3 is Al, Co, Mn, Zn, Cr, Fe, Mg, Sr, V, Ca, Ti, Y, Zr, Nb, Mo, Hf, Ta, W, Na, Sn, rare earth elements, or a combination thereof, and A is F, Cl, Br, I, S, P, or a combination thereof, and 1≤d1≤2, 0<e1≤1, 0<e2≤1, 0<e3≤1, and 0≤f1<2. Claim 21 delete Claim 22 In paragraph 12, the anode active material layer further comprises a solid electrolyte, and the solid electrolyte is a halide-based solid electrolyte. Claim 23 In claim 12, the lithium ion conductivity of the compound represented by the above chemical formula 1 is 1.0 x 10⁻⁶ -6 Anode with S / cm or higher. Claim 24 An all-solid-state battery comprising an anode according to any one of claims 12 to 20, 22, and 23; a cathode; and a solid electrolyte layer located between the anode and the cathode. Claim 25 In paragraph 24, the solid electrolyte layer comprises a sulfide-based solid electrolyte, and the sulfide-based solid electrolyte is an azirodite-type sulfide-based solid electrolyte, in a solid-state battery. Claim 26 In paragraph 24, the all-solid-state battery having a charging voltage of 4.5V or higher. Claim 27 In paragraph 24, the all-solid-state battery having a discharge voltage of 3.5V or less.
Citation Information
Patent Citations
Cathode active material for all-solid-state lithium secondary batteries
KR1020200023452A
Lithium halide-based nanocomposite, preparing method thereof, solid electrolyte comprising the same, and all-solid-state battery comprising the solid electrolyte
KR1020230174193A
